1992
DOI: 10.1038/355050a0
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic contribution to long-term potentiation revealed by the analysis of miniature synaptic currents

Abstract: Miniature excitatory synaptic currents were recorded from CA1 pyramidal cells in hippocampal slices to study the site of the persistent change in synaptic efficacy during long-term potentiation. Induction of long-term potentiation produced a large increase in the amplitude of these currents. Such a change in amplitude suggests an increase in postsynaptic transmitter sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
156
1
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(170 citation statements)
references
References 32 publications
12
156
1
1
Order By: Relevance
“…Quanta1 analyses (Bekkers and Stevens, 1990;Malinow and Tsien, 1990;Larkman et al, 1992;Liao et al, 1992;Manabe et al, 1992;Voronin, 1993;Kullmann, 1994) have indicated that all of the statistical parameters of quanta1 transmission-quanta1 size, q; number of available release units, n; and probability of quanta1 release, P-may be altered in LTP Morphological changes in dendritic spines could in principle affect any of these parameters (Carlin and Siekevitz, 1983;Harris and Stevens, 1989;Calverley and Jones, 1990;Edwards, 1991;Lisman and Harris, 1993;McNaughton, 1993;Bailey and Kandel, 1993). Thus, for example, if quanta1 release saturates available receptors at central synapses (Redman, 1990;Korn and Faber, 1991;Tong and Jahr, 1994), spine growth incorporating more postsynaptic receptors could yield increased q.…”
Section: Discussionmentioning
confidence: 99%
“…Quanta1 analyses (Bekkers and Stevens, 1990;Malinow and Tsien, 1990;Larkman et al, 1992;Liao et al, 1992;Manabe et al, 1992;Voronin, 1993;Kullmann, 1994) have indicated that all of the statistical parameters of quanta1 transmission-quanta1 size, q; number of available release units, n; and probability of quanta1 release, P-may be altered in LTP Morphological changes in dendritic spines could in principle affect any of these parameters (Carlin and Siekevitz, 1983;Harris and Stevens, 1989;Calverley and Jones, 1990;Edwards, 1991;Lisman and Harris, 1993;McNaughton, 1993;Bailey and Kandel, 1993). Thus, for example, if quanta1 release saturates available receptors at central synapses (Redman, 1990;Korn and Faber, 1991;Tong and Jahr, 1994), spine growth incorporating more postsynaptic receptors could yield increased q.…”
Section: Discussionmentioning
confidence: 99%
“…However, Manabe et al 119921 found that LTP produces a marked increase of spontaneous miniature postsynaptic potentials in CA1 neurons, which suggests a postsynaptic change, perhaps at the receptor level. Of course, the findings of Manabe et al [1992] do not rule out a simultaneous presynaptic change.…”
Section: Ltp Maintenancementioning
confidence: 99%
“…(1) The amplitude of miniature EPSCs (mEPSCs) is increased (decreased) during LTP (LTD) (Manabe et al, 1992;Oliet et al, 1996). (2) Hippocampal LTP (LTD) is accompanied by a higher (lower) sensitivity of the postsynaptic membrane for exogenously applied agonists (Davies et al, 1989;Kandler et al, 1998).…”
Section: Abstract: Caged Compounds; Expression Site; Ltp; Ltd; Neocomentioning
confidence: 99%